Antibiotic Resistance in Klebsiella Pneumoniae and Its Impact in Mixed Type Isolates (Iraqi Journal of Medical Sciences, 2024)
Background: The Klebsiella pneumoniae (K. pneumoniae) is part of the healthy human microbiome, providing a potential reservoir for infection. It is most prevalent in healthcare settings and it is a significant nosocomial pathogen, leading to infections among hospitalized patients. Objective: To investigate the prevalence of multidrug resistance (MDR), extensively drug resistance (XDR) and pan-drug resistance (PDR) patterns among K. pneumoniae with their importance in mixed type isolates.Methods: This study is a cross-sectional investigation that included a total of 132 K. pneumoniae isolates, isolated from different infections collected from bacteriology laboratories located in six government hospitals in Baghdad. The Vitek2 system confirmed the bacterial and antibiotic susceptibilities.Results: The results showed that 106/132 (80.3%) of the isolates were pure K. pneumoniae, and 26/132 (19.7%) were mixed type isolates (K. pneumoniae plus other bacteria). It was found that the isolates were most resistant to beta-lactamase drugs and sulfonamide, such as Ticarcillin (97%), Piperacillin (92%), Ceftazidime (90%), Ticarcillin/Clavulanic acid (83%), Azatreonem (86%), and Trimethoprim/Sulfamethoxazole (86%). The antibiotic susceptibility patterns showed that 40/132 (30.3%) had possible XDR, 30/132 (22.7%) had MDR, and 16/132 (12.1%) had possible PDR. In the present study, burn infections followed by respiratory secretions revealed isolates with higher antibiotic resistance.Conclusion: The study revealed that high incidence of XDR and MDR patterns compared to previous studies conducted in Iraq in recent years. The co-existence of two or more bacterial species may lead to syntrophic interactions. The emergence of antibiotic-resistant strains among mixed strains has increased the severity of polymicrobial infection.Keywords: Klebsiella pneumoniae, antibiotics susceptibility patterns, poly-microbial infections. Citation: Fouad NA, Totl KJ. Antibiotic resistance in Klebsiella Pneumoniae and its impact in mixed type isolates. Iraqi JMS. 2024; 22(2): 369-376. doi: 10.22578/IJMS.22.2.22
Keywords: Klebsiella pneumoniae; antibiotics susceptibility patterns; polymicrobial infections